1991
DOI: 10.1177/002224379102800306
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-National Assessment of the Reliability and Validity of the CETSCALE

Abstract: Though numerous calls have been made for the cross-national validation of measures used in international research, they have gone mostly unanswered. Recent research suggests that one construct and associated measure that may have great potential for international consumer research are consumer ethnocentrism and the CETSCALE, respectively. However, the CETSCALE was developed and validated with samples of U.S. consumers only. The authors assess the psychometric properties and nomological validity of the CETSCALE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
240
3
8

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 253 publications
(267 citation statements)
references
References 15 publications
16
240
3
8
Order By: Relevance
“…Therefore, this study examines the cross-cultural applicability of a scale for profiling consumers' decision-making styles. The study is consistent with the stream of research that addresses the crosscultural generalizability of consumer behavior measurement scales and procedures (see Netemeyer, Durvasula, and Lichtenstein 1991).…”
Section: Cross-cultural Generalizability Of a Scale For Profiling Consupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, this study examines the cross-cultural applicability of a scale for profiling consumers' decision-making styles. The study is consistent with the stream of research that addresses the crosscultural generalizability of consumer behavior measurement scales and procedures (see Netemeyer, Durvasula, and Lichtenstein 1991).…”
Section: Cross-cultural Generalizability Of a Scale For Profiling Consupporting
confidence: 83%
“…Researchers have suggested that most measures developed in consumer behavior are validated using U.S. samples and, therefore, might apply only to the United States (Green and White 1976). Perhaps for this reason, researchers have started to investigate cross-cultural dimensions of consumer behavior constructs (e.g., Andrews, Lysonski, and Durvasula 1991;Lysonski and Pollay 1990;Netemeyer, Durvasula, and Lichtenstein 1991). As the global marketplace becomes more integrated and consumer specialists develop an international focus, developing useful scales to profile consumer decision-making styles in other cultures becomes important.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining consistently high quality services is a powerful means of increasing the overall performance of a global Asian enterprise . Measures with sound psychometric properties across Asian countries will facilitate service marketing strategies in Asian markets (Netemeyer et al, 1991 All in all, the present study highlights the crucial role of service quality in enhancing social, firm, and individual performances by meeting customer needs during service co-creation. This understanding makes an important contribution to service research.…”
Section: Discussionmentioning
confidence: 75%
“…For example, existing studies find that ethnocentric consumers underestimate foreign product attributes, which normally include quality, design, and package, whereas they have an overestimation towards local products (Sharma et al, 1995;Siamagka & Balabanis, 2015). Studies in developed countries suggest that ethnocentric consumers, generally, are proud of domestic products and judge them more favourable than foreign products; therefore, they are less likely to purchase foreign products (Netemeyer, Durvasula, & Lichtenstein, 1991;Sharma et al, 1995). Ethnocentric consumers normally have purchase intention towards domestic products or feel that it is morally wrong to buy foreign products.…”
Section: Consumer Ethnocentrismmentioning
confidence: 99%